Implementasi Payment Gateway Dengan SNAP Midtrans (Studi Kasus Pada Website AC Tiam) - Andreas, Ryan; Widayanti, Riya (Jurnal SISKOM-KB (Sistem Komputer dan Kecerdasan Buatan), 2024)
AC Tiam is a business that operates in the field of water services conditioner. Currently AC Tiam is still carrying out business activities manually, these activities such as the process of ordering services using chat and using books as a recording tool data, this method is certainly not effective because it allows errors to occur in the process recording service details and allowing loss of books. Apart from that, in terms of methods payment, AC Tiam still accepts cash payments, namely the customer hands over the money to the technician after the service process is complete. cash payment processes have several The downside is that physical money is vulnerable to security risks such as theft or loss. Based on these problems, the author designed a service system based on AC services a website equipped with a payment gateway feature. In the process of designing this information system, the author will use several data collection methods, namely observation, interviews, and studies References. The development method chosen for this system is Process Prototyping This system development uses ReactJs as the frontend framework, NodeJS as the backend and MySQL as database. The results of the research are an information system prototype website-based AC service which is equipped with a payment gateway feature. Expected system proposals can improve the quality and service of ordering AC services starting from the order process, payment to bookkeeping.